Introduction of risk management in the functional activity of public institutions (Regional aspects of productive forces development of Ukraine, 2020)
Introduction. The article substantiates the scientific and organizational principles of introducing risk management tools into the functional activities of public institutions as a means of innovation and increasing the competitive status of government institutions at both the state and regional levels. The risks related to the provision of public services and their resource support are structured and identified, as well as the algorithm of their management is substantiated.Goal. To substantiate the essential determinants of risk management and scientific and organizational principles of its introduction into the functional activity of public institutions at the macroeconomic and regional levels.Methods. Within the framework of the scientific publication the methods of historical, systematic, comparative, structural analysis, abstract-logical generalization are used.Results. The paper substantiates the architecture of risk management in the public service, proves that it should be integrated into all subsystems of administrative management of the public institution and be an integral part of the management decision-making process. The mechanism of corruption risk management is considered, which should include: development of a strategy or program for anticipation of possible areas of corruption risks, assessment of corruption risks, development of a mechanism for responding to corruption risks, monitoring the effectiveness of the anti-corruption mechanism.Conclusions. The main provisions of the scientific article will help build an innovative, competitive, professional, transparent, non-corrupt, prestigious, needs-oriented public service.